Effect of a low-carbohydrate diet versus a low-fat, calorie-restricted diet on adipokine levels in obese, diabetic participants - Vetter M (Dove Medical Press, 2010)
Marion L Vetter1,2,3, Alisha Wade1, Leslie G Womble3, Cornelia Dalton-Bakes1, Thomas A Wadden3, Nayyar Iqbal1,21Division of Endocrinology, Diabetes, and Metabolism, Department of Medicine, Hospital of the University of Pennsylvania, Philadelphia, PA, USA; 2Division of Endocrinology, Department of Medicine, Philadelphia Veterans Affairs Medical Center, Philadelphia, PA, USA; 3Department of Psychiatry, Center for Weight and Eating Disorders, University of Pennsylvania School of Medicine, Philadelphia, PA, USAAbstract: The effect of dietary macronutrient composition on adipokine concentrations remains unclear. Greater reductions in leptin have been reported in participants who followed low-carbohydrate versus low-fat diets, although these studies did not adjust for the important effects of weight loss on adipokines. We investigated the effect of macronutrient composition on adipokine levels in 144 obese, diabetic participants who were randomly assigned to a low-carbohydrate (<30 g/day) or low-fat diet (≤30% of calories from fat with a deficit of 500 kcal/day). Weight, adipokines, and dietary intake were assessed at baseline and 6 months. Complete data were available for 79 participants. At month 6, weight, leptin, adiponectin, and tumor necrosis factor-a concentrations did not differ significantly between groups (P > 0.05 for all variables). However, significant changes in leptin and adiponectin occurred over time (P < 0.001 and P < 0.012, respectively). Modest weight loss, rather than macronutrient composition, likely accounted for the favorable changes observed in leptin and adiponectin over time.Keywords: diet, adipokine, obesity, diabetes, carbohydrate, hormone